Women and Men in Swiss vocational education - Borkowsky, Anna (Swiss Journal of Educational Research, 2018)
Switzerland is a country where vocational education is highly developed. The majority of the young people achieve their upper secondary education through the «dual» system of apprenticeship. Swiss vocational education leads to a socially well defined «Occupation» or «Profession», which is well recognized by employers on the labor market as well as by society as a whole. The Swiss system of occupations is also remarkable for its high degree of gender segregation. The organizing principles of vocational education «Beruf» and the work-based part of the apprenticeships both work against women.